(untitled) (Географический вестник=Geographical bulletin, 2017)
Приводятся результаты исследований по выявлению территорий высокой природоохранной ценности одного из наиболее аграрно освоенных районов Пермского края. На территории района выделены ключевые ботанические территории, сельскохозяйственные территории высокой природоохранной ценности, ряд ключевых биотопов, описаны новые места обитания редких видов растений, занесенных в Красную книгу. Даны рекомендации по расширению сети ООПТ и формированию полноценного экологического каркаса района. К л ю ч е в ы е с л о в а: территории высокой природоохранной ценности; ключевые ботанические территории; ключевые биотопы HIGH CONSERVATION VALUE TERRITORIES OF BEREZOVSKIY DISTRICT OF PERM REGION In the article results of researches on revealing of high conservation value territories of one of the most agrarian mastered areas ofPermregion are presented. Key botanical territories, agricultural territories of high conservation value, key biotops, new places of dwelling of rare species of the plants included in the Red book are described. Recommendations about expansion of nature protected areas and formation of a high-grade ecological network of district are given. K e y w o r d s: high conservation value territories; key botanical territories; key biotops.